2022
DOI: 10.3389/fcvm.2022.806743
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Beta Blockers on the Long-Term Prognosis of Patients With Premature Atrial Complexes

Abstract: AimsPremature atrial complexes (PACs) have been reported to increase the risk of adverse cardiovascular outcomes. Beta blockers at low dosages may help to reduce PAC symptoms, but it is unclear whether they can improve long-term outcomes.MethodsPatients enrolled from a Holter cohort in a medical referral center were stratified into high-burden (≥100 beats/24 h) and low-burden (<100 beats/24 h) sub-cohorts, and propensity score matching between treatment groups and non-treatment groups was conducted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Asymptomatic individuals with atrial premature contractions do not need any therapy, whereas symptomatic patients are counselled to avoid precipitants, such as alcohol and caffeine. Persistent symptoms are treated with beta blockers or catheter ablation 44 . For patients with premature ventricular contractions, risk factors and precipitants, such as alcohol, caffeine, uncontrolled hypertension, and thyroid abnormalities, are corrected.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Asymptomatic individuals with atrial premature contractions do not need any therapy, whereas symptomatic patients are counselled to avoid precipitants, such as alcohol and caffeine. Persistent symptoms are treated with beta blockers or catheter ablation 44 . For patients with premature ventricular contractions, risk factors and precipitants, such as alcohol, caffeine, uncontrolled hypertension, and thyroid abnormalities, are corrected.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Standardized therapeutic management of nonsustained atrial arrhythmia is not currently consensual. Regarding a rhythm control strategy using beta-blockers, prospective interventional trials are lacking, and observational studies suggest a lack of benefit in terms of AF occurrence and ischemic stroke ( Huang et al, 2022 ). Invasive PAC ablation is an effective strategy regarding the PAC burden ( Wang et al, 2017 ), but its value in improving clinical prognosis has not been depicted.…”
Section: Current Limitations and Clinical Implicationsmentioning
confidence: 99%
“…The Japanese Circulation Society/The Japanese Heart Rhythm Society guidelines indicate the use of beta-blockers for symptomatic atrial premature contractions in Class IIa [11]. Multiple atrial premature contractions are associated not only with the development of AF but also with cardiovascular mortality [12], and beta-blockers for atrial premature contractions have been shown to be effective in reducing AF [13].…”
mentioning
confidence: 99%